2005
DOI: 10.2214/ajr.184.6.01841731
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Reviewers: Comparison of Review Quality and Reviewer Characteristics at the American Journal of Roentgenology

Abstract: The highest-rated AJR reviewers tended to be young and from academic institutions. The quality of peer review did not correlate with the sex, academic rank, or subspecialty of the reviewer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 14 publications
4
41
1
1
Order By: Relevance
“…Primack et al (2009) found no evidence of a difference among genders. Kliewer et al (2005), Ceci &Williams (2011) andWalker (2015) confirmed the findings of Primack et al using different samples. More recent work indicates that gender does not appear to be a bias-inducing factor.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Primack et al (2009) found no evidence of a difference among genders. Kliewer et al (2005), Ceci &Williams (2011) andWalker (2015) confirmed the findings of Primack et al using different samples. More recent work indicates that gender does not appear to be a bias-inducing factor.…”
Section: Introductionsupporting
confidence: 87%
“…The verdict about age is also unclear. While Kliewer et al (2005) discovered that (especially younger) age has an effect on the review outcome, Primack et al (2009) found the opposite to be true. Age will not be studied in the present study, since we were unable to collect reliable data about age.…”
Section: Introductionmentioning
confidence: 99%
“…In a logistic regression analysis the only significant characteristics were younger age and those with training in epidemiology or statistics. Other authors have found no significant correlation between quality of reviews and sex, years of reviewing and academic rank (Kliewer et al, 2005).…”
Section: What Makes a Good Reviewer?mentioning
confidence: 88%
“…However, the evidence suggests that younger reviewers make better quality reviews (Stossel, 1985;Evans, McNutt, Fletcher & Fletcher, 1993;Kliewer, Freed, DeLong, Pickhardt & Provenzale, 2005). Research training and postgraduate qualifications were not associated with review quality.…”
Section: What Makes a Good Reviewer?mentioning
confidence: 99%
“…Dergimizin bilimsel performansını arttırma ve "peer-review" uygulamalarını optimize etme çalışmalarının "kanıta-dayalı yayıncılık" prensipleri (8) çerçevesinde yürütülmesinin uygun olacağına inanıyoruz (9)(10)(11)(12). Elimizde 2001'den bu yana biriken ve sürekli yenilenen veri havuzunun analiz edilmesi, negatif ve pozitif yanlarının tespit edilmesi, gelecek için strateji belirlenmesinde yararlı olabilir.…”
unclassified